Pelatihan Kelompok Peduli Hipertensi sebagai Upaya Peningkatan Kualitas Hidup Pasien Hipertensi di Rajamandala Kulon Bandung Barat - Citra Windani Mambang Sari (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2018)
Health problems in West Bandung regency is very complex. One of them is Hypertension is one of the chronic diseases that the number of events and complications that resulted in increasing from time to time. The condition of limited health personnel requires the involvement of health cadres as community empowerment so that people understand about hypertension. In addition, people do not regularly check blood pressure. This devotional activity is aimed at implementing community-based programs that facilitate the community in forming hypertension community groups and add knowledge and good behavior about the management of Hypertension in the Village of Rajamandala Kulon, West Bandung Regency. The methodology of research was one group pre post design with group training care hypertension to cadres and community leaders who measured knowledge, attitude and self-efficacy before and after training. The instruments used are knowledge, attitude and self-efficacy based on previous research. Data analysis uses frequency distribution and Wilcoxon. The result of this research was a significant difference of knowledge, attitude and group self-efficacy about Hypertension (p value <0,05). Through the formation of community-based Hypertension community groups that can be applied independently by the community through health cadres with the supervision of health workers who can impact on improving the health status of the people of West Bandung regency.